Removal of a separated endodontic instrument in the mesiolingual canal of a lower second molar: case report - Duarte, Marcella Mattos (2022)
During endodontic treatment, incidents such as instrument fracture inside the root canals can happen. Such complications are caused by torsion or fatigue of the instrument. Therapeutic alternatives include chemical-mechanical preparation up to the fractured fragment; the chemical-mechanical preparation surpassing the fragment; or removal of the instrument via the canal or by apical microsurgery. This paper aims to report the case of a patient referred for endodontic treatment of tooth 47, presenting a fractured endodontic instrument in one of the canals. It was described by the first operator that, during the chemical-mechanical preparation, a reciprocating instrument fractured in the mesiolingual canal. After clinical and radiographic examinations, it was decided to include in the treatment planning the attempt to remove the fragment via the canal, with the aid of operative microscopy and ultrasonic inserts. During the process, the fractured instrument broke again. As its visualization was still maintained, the removal attempt was continued. After the successful procedure, endodontic treatment was performed and completed. After a five-month observation period, the patient remained asymptomatic. Removal of a fractured endodontic instrument via canal is generally the choice option for such complications, as the shaping and disinfection of the canals are more efficient, enabling a high rate of treatment success. However, the professional must pay attention to avoid further accidents or procedural errors. It was concluded that the removal of the endodontic instrument fragment was performed satisfactorily, being a valid attempt for greater predictability of endodontic treatment, when the benefits of the procedure outweigh the risks.